Bending Strength of Welded Joints in TMCP Steel Square Tubular Profiles â€œTâ€ Connexions - Dalcin, Rafael Luciano; Machado, Ivan Guerra; Gonzalez, Arnaldo Ruben; Mazzaferro, Cintia Cristiane Petry (International Journal of Engineering and Technology, 2016)
The use of DOMEX 700 MCTM steel weldments is still little explored, due to some concern of the validity of the rules imposed by several standards and Codes for this class of steel. This material has low ductility and consequently the relation between tensile strength and yield strength is significantly lower than ordinary structural steels. For this reason, the instability phenomena are more critical than the instability phenomena of ordinary structural steels. Therefore, the aim of this study was to obtain detailed data on the mechanical efficiency of joints welded by GMAW. Six different heat inputs were used on square tubular profiles of TMCP steel. The tubular profiles were placed as a column/beam weldment with transverse and longitudinal welds positioned in relation to the loading axis. Twelve welded structures were instrumented with extensometer and tested in simple bending. Comparing the obtained data, it was verified that longitudinal welded joints presented higher bending strength than transversal welded joints. In the case of longitudinal joints, two weld beads were subjected to bending efforts, and in the case of transverse joints, only one weld bead resisted bending forces.
Keywords: GMAW; TMCP Steel; Tubular Profile; Welded Joint Bending Strength.